Evasion of Host Antiviral Innate Immunity by Paramyxovirus Accessory Proteins - Wang, Chongyang; Wang, Ting; Duan, Liuyuan; Chen, Hui; Hu, Ruochen; Wang, Xiangwei; Jia, Yanqing; Chu, Zhili; Liu, Haijin; Wang, Xinglong; Zhang, Shuxia; Xiao, Sa; et al. (Frontiers in Microbiology, 2022)
For efficient replication, viruses have developed multiple strategies to evade host antiviral innate immunity. Paramyxoviruses are a large family of enveloped RNA viruses that comprises diverse human and animal pathogens which jeopardize global public health and the economy. The accessory proteins expressed from the P gene by RNA editing or overlapping open reading frames (ORFs) are major viral immune evasion factors antagonizing type I interferon (IFN-I) production and other antiviral innate immune responses. However, the antagonistic mechanisms against antiviral innate immunity by accessory proteins differ among viruses. Here, we summarize the current understandings of immune evasion mechanisms by paramyxovirus accessory proteins, specifically how accessory proteins directly or indirectly target the adaptors in the antiviral innate immune signaling pathway to facilitate virus replication. Additionally, some cellular responses, which are also involved in viral replication, will be briefly summarized.